Performance of growing male quails under different Complete Feeds and Floor Sorts - Muljowati, Sri; Mufti, M (ANIMAL PRODUCTION, 1999)
A research entitled âPerformance of Growing Male Quails Under Different Complete Feeds and Floor Sortsâ has been conducted in experimental farm, Faculty of Animal Husbandry Unsoed Â Purwokerto.Â  The objective of the study is to find out the best floor sort and complete feed for performance of growing male quails. One hundred and fifty male quails at three weeks old were used in this study. Split Plot Design were used in this research. Floor sortsÂ  were used asÂ  maintreatments and they consists of L1 (litter floor) and L2 (wire floor) Complete feeds were used as subtreatment and they consists ofÂ  P1 (AD 51), P2 (CP 511), P3(B 11) and P4 (BR 1). Deck levels were used as deckÂ  andT1 (high), T2 (meden) and T3 (low deck). Statistical analyses showed that complete feeds had significant effect (P<0.05) on feed consumption but not significant on body weight, growth and feed conversion. Floor sorts and their interactionÂ  with the complete feedsÂ  had not significant on the performance of the birds. It can be conclused that during growing period, P1 (AD 51) gave better performance and for floor shorts, either litter or wire can be used to growing male quails. (Animal Production 1(2): 90-98 (1999)Â Key Words: Quails, complete feed commercial, floor